White matter hyperintensities burden in the frontal regions is positively correlated to the freezing of gait in Parkinson’s disease - Zou, Xiaoya; Dong, Zhaoying; Chen, Xinwei; Yu, Qian; Yin, Huimei; Yi, Li; Zuo, Hongzhou; Xu, Jiaman; Du, Xinyi; Han, Yu; Zou, Dezhi; Peng, Juan; et al. (Frontiers in Aging Neuroscience, 2023)
Objective: Previous studies have reported that white matter hyperintensities (WMHs) are associated with freezing of gait (FOG), but it is not clear whether their distribution areas have correlations with FOG in Parkinson's disease (PD) and the potential influencing factors about WMHs. Methods: Two hundred and forty-six patients with PD who underwent brain MRI were included. Participants were divided into PD with FOG (n=111) and PD without FOG (n=135) groups. Scheltens score was used to assess the WMHs burden in the areas of deep white matter hyperintensity (DWMHs), periventricular hyperintensities (PVHs), basal ganglia hyperintensities (BGHs), and infratentorial foci of hyperintensities (ITF). Whole brain WMHs volume was evaluated by automatic segmentation. Binary logistic regression was used to evaluate relationships between WMHs and FOG. The common cerebrovascular risk factors that may affect WMHs were evaluated by mediation analysis. Results: There were no statistical differences between PD with and without FOG groups in whole brain WMHs volume, total Scheltens score, BGHs, and ITF. Binary logistic regression showed that the total scores of DWMHs (OR=1.094; 95% CI, 1.001, 1.195; p=0.047), sum scores of PVHs and DWMHs (OR=1.080; 95% CI, 1.003, 1.164; p=0.042), especially the DWMHs in frontal (OR=1.263; 95% CI, 1.060, 1.505 p=0.009), and PVHs in frontal caps (OR=2.699; 95% CI, 1.337, 5.450; p=0.006) were associated with FOG. Age, hypertension, and serum alkaline phosphatase (ALP) are positively correlated with scores of DWMHs in frontal and PVHs in frontal caps. Conclusions: These results indicate that WMHs distribution areas especially in the frontal of DWMHs and PVHs play a role in PD patients with FOG.